In MMTV-Her-2/neu transgenic mammary tumors the absence of caveolin-1−/− alters PTEN and NHERF1 but not β-catenin expression - Cuello Carrión, Fernando Darío (2013)
In a recent study, we have shown that in mammary tumors from mice lacking the Cav-1 gene, there are alterations in specific heat shock proteins as well as in tumor development. With this in mind, we have now investigated other proteins in the same mammary mouse tumor model (Her-2/neu expressing mammary tumors from Cav-1 wild type and Cav-1 null mice), to further comprehend the complex tumor-stroma mechanisms involved in regulating stress responses during tumor development. In this tumor model the cancer cells always lacked of Cav-1, so the KO influenced the Cav-1 in the stroma. By immunohistochemistry, we have found a striking co-expression of β-catenin and Her-2/neu in the tumor cells. The absence of Cav-1 in the tumor stroma had no effect on expression or localization of β-catenin and Her-2/neu. Both proteins appeared co-localized at the cell surface during tumor development and progression. Since Her-2/neu activation induces MTA1, we next evaluated MTA1 in the mouse tumors. Although this protein was found in numerous nuclei, the absence of Cav-1 did not alter its expression level. In contrast, significantly more PTEN protein was noted in the tumors lacking Cav-1 in the stroma, with the protein localized mainly in the nuclei. P-Akt levels were relatively low in tumors from both Cav-1 WT and Cav-1 KO mice. There was also an increase in nuclear NHERF1 expression levels in the tumors arising from Cav-1 KO mice. The data obtained in the MMTV-neu model are consistent with a role for Cav-1 in adjacent breast cancer stromal cells in modulating the expression and localization of important proteins implicated in tumor cell behavior.